PV Array Simulation with Single Diode Equivalent Circuit Considering Series and Shunt Resistance - Reformasi, Fransiskus Dani; Santika, Maria Enggar; Putra, Nabil Dwi Gusna; Robbi, Ivandra Fike Amanta (Universitas Muhammadiyah Yogyakarta, 2025)
This study analyzes the output characteristics of solar panels using three modeling approaches, namely the Single Diode Model (SDM), the Ideal Single Diode Model (ISDM), and the Newton–Raphson (NR) method, and compares them with the reference model from the MATLAB library. The performance of each model is tested under various irradiation and temperature conditions. The results indicate that the ISDM model, implemented using MATLAB Simulink blocks, exhibits noticeable deviation from reference due to the neglect of shunt resistance (R_sh) and series resistance (R_s) effects. The SDM model with the Matlab Simulink block provides better accuracy but still shows slight discrepancies caused by algebraic loops during simulation. Among the three methods, the Newton–Raphson method yields results that match the reference most closely, demonstrating minimal error at the maximum power point. This confirms that the NR method more accurately represents PV characteristics and behavior compared to the SDM and ISDM. Therefore, this method can be relied upon for PV system simulation and optimization applications under varying operating conditions.